Unusual reversible elastomeric gels from Nostoc commune - Rodriguez, S (2017)
Nostoc commune cyanobacteria grow in extreme conditions of desiccation and nutrient-poor soils. Their colonies form spherical gelatinous bodies are composed of a variety of polysaccharides that allow them to store water and nutrients. In this paper, we study this type of biological gel that shows characteristics of both chemical and physical gels. The structure of this gel was assessed by means of scanning electron microscopy, plate-plate rheometry, Fourier transform infrared spectroscopy and absorption/desorption tests. The storage modulus of this gel was found to be frequency independent, as is usual for chemical gels. The stress sweeps showed a reversible stress softening behaviour that was explained in terms of the physical nature of the interactions of this network. The high density of physical crosslinks probably allows this physical network to behave as a highly elastomeric chemical network, limiting the relaxation of individual chains. On the other hand, reversibility is associated with the physical nature of its bonds.